When does global mindset affect headquarters-subsidiary relationship? - Li, Jizhong; Jiang, Fuming; Travaglione, Tony (2020)
Drawing on the dynamic managerial capabilities perspective, we examine the effects of the global mindset of frontline managers on headquarters-subsidiary relationships and the moderating effects of their cognitive flexibility, overseas study experience, and exchanges with headquarters managers on the relationship. The analysis of dyadic data collected from managers at headquarters and subsidiaries of 312 Chinese multinational enterprises reveals that the frontline managers’ global mindset positively affects headquarters-subsidiary relationships. This effect is stronger when frontline managers exhibit higher cognitive personality flexibility and more overseas study experience but weaker when exchanges with headquarters managers become more frequent.